Identification of functional circRNA/miRNA/mRNA regulatory network for exploring prospective therapy strategy of colorectal cancer. Issue 12 (1st March 2020) - Xu, Dongping; Wu, Yutong; Wang, Xiufang; Hu, Xiaoyun; Qin, Wenyan; Li, Yalun; Wang, Yilin; Zhang, Zhen; Lu, Senxu; Sun, Tong; Wu, Zhikun; Fu, Dandan; et al.
Abstract: Circular RNA (circRNA) has been reported to have great scientific significance and clinical value in multiple cancers including colorectal cancer (CRC). However, the biological function of most circRNAs in CRC is still in its infancy. Herein, we discovered the differential expressed circRNAs (DECs) between CRC tissues and matched adjacent using deep RNA sequencing and further confirmed the DECs expression by combining with another Gene Expression Omnibus dataset. Furthermore, we validated the expression of the top four upregulated circRNAs (hsa_circ_0030632, hsa_circ_0004887, hsa_circ_0001550, and hsa_circ_0001681) in both of paired CRC tissues and CRC cell lines. Then, a circRNA/microRNA/messenger RNA regulatory network was established and the Gene Ontology analysis and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis showed these four circRNAs participated in various biological processed including apoptotic process and multiple metabolic processes. Moreover, based on the regulatory network, three bioactive compounds (pergolide, pivampicillin, and methylergometrine) for the treatment of CRC were also found. In conclusion, this study improved our understanding of circRNAs and may also facilitate the finding of promising targets and biomarkers in CRC. Abstract : In this study, we showed the differential expressed circRNA, circular RNA, (DECs) in colorectal cancer (CRC) tissues and matched adjacent normal tissues based on deep RNA sequencing and ensured the DECs expression by combining with GSE116589 and further validated the expression of four significantly upregulated circRNAs in both of paired CRC tissues and cell lines. Moreover, we constructed the circRNA/microRNA/messenger RNA regulatory network in CRC and analyzed the potential biological functions of DECs. Furthermore, three potential bioactive compounds for the treatment of CRC were also found based on the regulatory network.